2013
DOI: 10.1080/01690965.2012.662279
|View full text |Cite
|
Sign up to set email alerts
|

Learning words in a third language: Effects of vowel inventory and language proficiency

Abstract: This study examines the effect of L2 and L3 proficiency on L3 word learning. Native speakers of Spanish with different proficiencies in L2 English and L3 Dutch and a control group of Dutch native speakers participated in a Dutch word learning task involving minimal and non-minimal word pairs. The minimal word pairs were divided into 'minimal-easy' and 'minimal-difficult' pairs on the basis of whether or not they are known to pose perceptual problems for L1 Spanish learners. Spanish speakers' proficiency in Dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 42 publications
5
55
2
Order By: Relevance
“…Previous work on minimal pairs has found that novel word learning performance is lower for words that share segments for native and non‐native listeners (e.g., Escudero et al., ; Escudero, Simon, et al., , ; Papagno & Vallar, ). While our results revealed that accuracy for vowel minimal pairs was lower than for non‐minimal pairs, there was no difference in performance between consonant minimal pairs and non‐minimal pairs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous work on minimal pairs has found that novel word learning performance is lower for words that share segments for native and non‐native listeners (e.g., Escudero et al., ; Escudero, Simon, et al., , ; Papagno & Vallar, ). While our results revealed that accuracy for vowel minimal pairs was lower than for non‐minimal pairs, there was no difference in performance between consonant minimal pairs and non‐minimal pairs.…”
Section: Discussionmentioning
confidence: 93%
“…In explicit word learning tasks, adults have some difficulty distinguishing minimal word pairs (Escudero, Broersma, & Simon, ; Escudero, Simon, & Mulak, ; Papagno & Vallar, ). For instance, Escudero et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would suggest that, all else being equal, Finnish learners of German might accept fewer words spoken in a novel German accent than Swedish learners. b) In addition to native language background, knowledge of additional L2 languages with larger vowel inventories than the L1 may be beneficial for word recognition in an L2 with a similarly large vowel inventory [27]. Swedish is the second official language in Finland and a compulsory language taught at schools.…”
Section: Introductionmentioning
confidence: 99%